Genetic reinstatement of RIG-I in chickens reveals insights into avian immune evolution and influenza interaction - Sid, Hicham; von Heyl, Theresa; Schleibinger, Sabrina; Klinger, Romina; Nabel, Leah Heymelot; Vikkula, Hanna; Guabiraba, Rodrigo; Guillory, Vanaique; Scicluna, Ryan; Alhussien, Mohanned Naif; Böhm, Brigitte; Schade, Benjamin; et al. (Frontiers in Immunology, 2025)
Retinoic acid-inducible gene I (RIG-I) activates mitochondrial antiviral signaling proteins, initiating the antiviral response. RIG-I and RNF135, a ubiquitin ligase regulator, are missing in domestic chickens but conserved in mallard ducks. The chickens’ RIG-I loss was long believed to be linked to increased avian influenza susceptibility. We reinstated both genes in chickens and examined their susceptibility to infection with an H7N1 avian influenza virus. Uninfected RIG-I-expressing chickens exhibited shifts in T and B cells. At the same time, the H7N1 infection led to severe disease, persistent weight loss, and increased viral replication. The simultaneous expression of RIG-I and RNF135 potentiated the RIG-I activity and was associated with exacerbated inflammatory response and increased mortality without influencing virus replication. Additional animal infection experiments with two other avian influenza viruses validated these findings. They confirmed that the harmful effects triggered by RIG-I or RIG-I-RNF135-expression require a minimum degree of viral virulence. Our data indicate that the loss of RIG-I in chickens has likely evolved to counteract deleterious inflammation caused by viral infection and highlight an outcome of restoring evolutionary lost genes in birds.